Enhanced Phytoextraction by As Hyperaccumulator Isatis cappadocica Spiked with Sodium Nitroprusside. Issue 4 (19th May 2017) - Souri, Zahra; Karimi, Naser
ABSTRACT: The present study investigates the possible role of exogenous nitric oxide (NO) supplementation as sodium nitroprusside (SNP), on increasing phytoextraction and phytoremediation ability of arsenic hyperaccumulator, Isatis cappadocica . Arsenate (500, 1000 and 1500 µM) alone or in combination with 200 µM SNP was given to hydroponically grown plants for 14 days. The highest level of arsenate (1500 µM) reduced the plant growth and chlorophyll content, while SNP alleviated these inhibitory effects. The application of SNP significantly increased the As concentration in the root (from 1004 to 1943 mg/kg) and shoots (from 1304 to 1859 mg/kg) compared with As-stressed plants. However, SNP treatment did not affect translocation factor value significantly in the As-stressed plants which shows enhancement of both As uptake and translocation under SNP application . This is the first study demonstrating the favorable effects of SNP on As tolerance, uptake, and accumulation of highly valuable As hyperaccumulator, I. cappadocica .